An AU-box motif upstream of the SD sequence of light-dependent psbA transcripts confers mRNA instability in darkness in cyanobacteria - Agrawal, Ganesh K. (Oxford University Press, 2001)
The psbA2 gene of a unicellular cyanobacterium, Microcystis aeruginosa K-81, encodes a D1 protein homolog in the reaction center of photosynthetic Photosystem II. The expression of the psbA2 transcript has been shown to be light-dependent as assessed under light and dark (12/12 h) cycling conditions. We aligned the 5′-untranslated leader regions (UTRs) of psbAs from different photosynthetic organisms and identified a conserved sequence, UAAAUAAA or the ‘AU-box’, just upstream of the SD sequences. To clarify the role of 5′-upstream cis-elements containing the AU-box for light-dependent expression of psbA2, a series of deletion and point mutations in the region were introduced into the genome of heterologous cyanobacterium Synechococcus sp. strain PCC 7942, and psbA2 expression was examined. A clear pattern of light-dependent expression was observed in recombinant cyanobacteria carrying the K-81 psbA2 –38/+36 region (which includes the minimal promoter element and a light-dependent cis-element with the AU-box), +1 indicating the transcription start site. A constitutive pattern of expression, in which the transcripts remained almost stable under dark conditions, was obtained in cells harboring the –38/+14 region (the minimal element), indicating that the +14/+36 region with the AU-box is important for the observed light-dependent expression. Point mutations analyses within the AU-box also revealed that changes in number, direction and identity (as assayed by adenine/uridine nucleotide substitutions) influenced the light-dependent pattern of expression. The level of psbA2 transcripts increased markedly in CG- or deletion-box mutants in the dark, strongly indicating that the AU- (AT-) box acts as a negative cis-element. Furthermore, characterization of transcript accumulation in cells treated with rifampicin suggests that psbA2 5′-mRNA is unstable in the dark, supporting the view that the light-dependent expression is controlled at the post-transcriptional level. We discuss various mechanisms that may lead to altered mRNA stability such as the binding of factor(s) or ribosomes to the 5′-UTR and possible roles of the AU-box motif and the SD sequence.